SUBSTANTIATION OF THE CONTENT OF THE PROGRAM OF PSYCHOPROPHYLAXIS OF THE EMOTIONAL BURNING SYNDROME THE SERVICE OFFICERS OF THE ENGINEERING TROOPS OF THE ARMED FORCES OF UKRAINE - Ryzhkova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The content of the author’s program of psychoprophylaxis of emotional burnout syndrome in servicemen of engineering troops of the Armed Forces of Ukraine is substantiated in the article. In particular, it is noted that the huge amount of engineering work carried out in large areas, short deadlines prove that the successful solution of engineering problems of combat operations requires intensive communication and causes deep shortterm emotional experiences, which can provoke emotional burnout of individual servicemen. Therefore, the system of professional training of servicemen is expected to use a system of specific methods of training, which are expressed in the development of professionally significant personality traits, adaptation to stressful factors of professional activity, and non-specific, characterized by the use of means and methods of emotional self-regulation. Psychoprophylaxis of emotional burnout of a serviceman is realized through the development of his skills of self-regulation, personality-oriented professional education, as well as his professional readiness. The program of psychoprophylaxis of emotional burnout is a holistic, sufficiently dynamic system, open for constant recovery, based on the idea of the development of the serviceman first as an individual and then as a specialist, a professional with a deep understanding of socio-cultural and educational situations. Achieving this goal is possible by synthesizing the main components of the personality of engineering troops serviceman: worldview, spiritual, moral and professional.